Institutional investors and home bias in Europe's Capital Markets Union - Zsolt Darvas; Dirk Schoenmaker (Bruegel, 2017)
Integrated capital markets facilitate risk sharing across countries. Lower home bias in financial investments is an indicator of risk sharing. We highlight that existing indicators of equity home bias in the literature suffer from incomplete coverage because they consider only listed equities. We also consider unlisted equites and show that equity home bias is much higher than previous studies perceived. We also analyse home bias in debt securities holdings, and euro area bias. We conclude that European Union membership may foster financial integration and reduce information barriers, which sometimes limit cross-country diversification. We calculate home bias indicators for the aggregate of the euro area as if the euro area was a single country and report remarkable similarity between the euro area and the United States in terms of equity home bias, while there is a higher level of debt home bias in the United States than in the euro area as a whole. We develop a new pension fund foreign investment restrictions index to control for the impact of prudential regulations on the ability of institutional investors to diversify geographically across borders. Our panel regression estimates for 25 advanced and emerging countries in 2001-14 provide strong support for the hypothesis that the larger the assets managed by institutional investors (defined as pension funds, insurance companies and investment funds), the smaller the home bias and thereby the greater the scope for risk sharing.
Keywords: C33; F21; F36; G11; G23; 330; home bias; institutional investment; portfolio diversification